2007
DOI: 10.1029/2006jd008209
|View full text |Cite
|
Sign up to set email alerts
|

Modeling study of ozone seasonal cycle in lower troposphere over east Asia

Abstract: On the basis of three mountain sites (Mount Tai, Hua and Huang) newly founded in east‐central China and several other sites from the Acid Deposition Monitoring Network in east Asia (EANET) and WMO World Data Centre for Greenhouse Gases (WDCGG), we investigate seasonal cycle of ozone over east Asia and its budgets in east‐central China by using a regional chemical transport model (NAQPMS). The observations show a striking ozone pattern of two sharp peaks in May‐June and September–October at three mountain sites… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
106
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 129 publications
(114 citation statements)
references
References 62 publications
8
106
0
Order By: Relevance
“…The EASM prevails in May-September every year, with strong southerlies bringing clean, warm, and moist air from the oceans to eastern China and rain belts that stretch for thousands of kilometers in the west-east direction in eastern China (Tao and Chen, 1987;Wang and Ding, 2008). Previous observational and modeling studies have shown that such patterns of winds and precipitation of the EASM influence the seasonal variations of O 3 in China (Chan et al, 1998;Li et al, 2007;He et al, 2008;Wang et al, 2011) and in the western Pacific region (Pochanart et al, 2002;Tanimoto et al, 2005;Yamaji et al, 2006). He et al (2008) analyzed the seasonal variations of O 3 concentrations measured over the period [2004][2005][2006] and found that O 3 concentrations peak in spring and autumn with a summer trough in central eastern China and the western Pacific, the areas that are influenced by clean air from the southern oceans during the summer monsoon.…”
Section: H Liao Et Al: Interannual Variations Of Summertime Surfacementioning
confidence: 99%
See 1 more Smart Citation
“…The EASM prevails in May-September every year, with strong southerlies bringing clean, warm, and moist air from the oceans to eastern China and rain belts that stretch for thousands of kilometers in the west-east direction in eastern China (Tao and Chen, 1987;Wang and Ding, 2008). Previous observational and modeling studies have shown that such patterns of winds and precipitation of the EASM influence the seasonal variations of O 3 in China (Chan et al, 1998;Li et al, 2007;He et al, 2008;Wang et al, 2011) and in the western Pacific region (Pochanart et al, 2002;Tanimoto et al, 2005;Yamaji et al, 2006). He et al (2008) analyzed the seasonal variations of O 3 concentrations measured over the period [2004][2005][2006] and found that O 3 concentrations peak in spring and autumn with a summer trough in central eastern China and the western Pacific, the areas that are influenced by clean air from the southern oceans during the summer monsoon.…”
Section: H Liao Et Al: Interannual Variations Of Summertime Surfacementioning
confidence: 99%
“…The formulation for calculating EASMI based on the GEOS-4 meteorological parameters was given in Zhu et al (2012). (Chan et al, 1998;Yamaji et al, 2006;Li et al, 2007;He et al, 2008;Wang et al, 2011). In western China, simulated O 3 exhibits maximum concentrations of 65 ppbv.…”
Section: East Asian Summer Monsoon Indexmentioning
confidence: 99%
“…A number of regional CTMs have been employed to study episodic chemical transport and transformations of Asian pollutants in springtime (e.g. Carmichael et al, 2003c;Zhang et al, 2003;Wang et al, 2006), and the seasonal cycle of surface O 3 in Eastern China (Li et al, 2007) and Japan (Yamaji et al, 2006). Results from the MICS-Asia regional model intercomparison study found that O 3 predictions for July over Central Eastern China differ by ∼20 ppbv among seven regional CTMs .…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies over Eastern China report that surface O 3 exhibits a narrow peak in early summer (May or June) and a sharp drop in July and August, based on measurements Published by Copernicus Publications on behalf of the European Geosciences Union. taken in downwind of Beijing (Ding et al, 2008;Lin et al, 2008c), at three mountaintop sites (Li et al, 2007), and at a rural site near Shanghai (Xu et al, 2008). Previous studies have suggested that the East Asia monsoon is responsible for the observed summer minimum of boundary layer O 3 along the west Pacific coast (Liu et al, 2002;He et al, 2008, and references therein).…”
Section: Introductionmentioning
confidence: 99%
“…The model has been used to study issues related to transport of air pollutants and related chemical processes, the interaction between mineral aerosols and acid rain over east Asia on a regional scale (Huang et al 1995;Wang et al 2002;Li et al 2007), and the impact of mobile sources on air quality in Beijing on an urban scale (Wu et al 2010). Compared with the sensitive analysis method employing intermittent emission, the online tagged method is an alternative and more efficient approach to evaluating the importance of various tagged regions.…”
Section: Air Pollutant Tagged Methodsmentioning
confidence: 99%